Pendidikan Kesehatan Reproduksi di Sekolah - Adhetya Uberty (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Adolescents generally face problems regarding sexuality and reproductive health due to limited and lack of information and advocacy, no access to youth-friendly services, limited government institutions that specifically deal with youth, no laws that accommodate youth rights, and no reproductive health curriculum for adolescents. Correct knowledge and understanding of reproductive health can be a provision for healthy and responsible behavior. The purpose of this community service activity is to provide benefits for adolescents to have knowledge and awareness of the importance of reproductive health as an effort to maintain their reproductive health. The method used is lecture, question and answer and discussion. The result is that adolescents obtain information and there is an increase in adolescent knowledge about reproductive health, so that adolescents obtain the right information as a provision to behave and behave in a healthy manner during the physical maturation process.